Microalbuminuria as a predictor of patient outcome in pediatric intensive care unit - Tariq, Syed; Mateen, Marwah; Ashraf, Mohammad; Wani, Safoora; Bhat, Javaid Ahmad (International Journal of Contemporary Pediatrics, 2022)
Background: Critically ill children have disturbed milieu interior and these disturbances can be estimated by measuring how much apart one or many physiologic variables are from the normal range. In critical care units, predicting patients' outcomes is vital to the intensivist. It allows planning early aggressive therapeutic interventions, optimum resource allocation and appropriate family and patient counselling. Methods: The study was conducted in the post graduate department of pediatrics and neonatology of tertiary care hospital. All patients admitted to our PICU for any critically ill ailment were classified into three groups. Results: In our study of 250 patients, study groups were divided into three groups. Group 1 patients with sepsis; group 2 patients with SIRS and group 3 patients without sepsis and SIRS. Ninety-four patients belonged to group 1; 78 belonged to group 2 and 78 belonged to group 3. There were 42, 36 and 27 females in group 1, group 2 and group 3, respectively. Most patients resided in district Kupwara. Most cases had respiratory system involvement. The median albumin creatinine ratio within 6 hours of admission (ACR1) and at 24 hours was 148 mg/g and 97 mg/g, respectively, among survivors and 199.2 and 287 among non-survivors. There were 30 deaths in group 1, 11 deaths in group 2 and 5 deaths in group 3. Conclusions: Microalbuminuria was found in 78.8% of critically ill children at admission. Urine albumin creatinine ratio at 6 and 24 hours of PICU stay was assessed to predict the degree of severity and mortality. It was found to have 88.5% sensitivity and 62.3% specificity.